Selection decisions among reindeer herders in Finland - Muuttoranta, Kirsi; Mäki-Tanila, Asko (Rangifer, 2011)
Selection of breeding animals is a tool to improve the revenues in animal production. Information about selection practices and criteria are essential in assessing the possibilities for systematic selection schemes. Attitudes of reindeer herders towards use of selection in improving production were investigated by means of interviews. We interviewed the managers of reindeer herding cooperatives concerning their selection decisions. Fortyfive out of 56 managers answered to the semi-structured questionnaire. Among herding operations, selection of breeding animals was regarded by managers as critical for calf’s autumn weight and survival. The main selection criteria were calf’s health, vigour, body size and muscularity, dam or dam line, and maternal care. Hair quality and hair length were important as well, while such often quoted traits as antler characteristics, e.g. early shedding of antler velvet and thick antler bases, were unimportant. The results show that reindeer herders i) acknowledge the importance and effects of selective breeding, and ii) have empirical knowledge to list the most important selection criteria.
Keywords: breeding objectives; Finland; Rangifer tarandus; reindeer; reindeer herders; selection decisions; selective breeding